The Pharmacopsychometric Triangle to Illustrate the Effectiveness of T-PEMF Concomitant with Antidepressants in Treatment Resistant Patients: A Double-Blind, Randomised, Sham-Controlled Trial Revisited with Focus on the Patient-Reported Outcomes. (7th June 2011) - Bech, P.; Gefke, M.; Lunde, M.; Lauritzen, L.; Martiny, K.
Abstract : Background . Our T-PEMF trial has been revisited with focus on the pharmacopsychometric triangle in which effect size is used when comparing wanted versus unwanted clinical effects and quality of life as outcomes. In this analysis, we have especially focused on the self-reported HAM-D6 . Methods . The antidepressive medication which the patients were resistant to was kept unchanged during the five weeks of active versus sham T-PEMF. Results . In total 21, patients received active T-PEMF, and 19 patients received sham T-PEMF. The effect size was 1.02 and 0.90, respectively, on HAM-D6 and HAM-D6 -S. Concerning side effects, the active T-PEMF reduced the baseline score on concentration problems with an effect size of 0.44 while inducing more autonomic symptoms than sham T-PEMF with an effect size of −0.41. The advantage of active over sham T-PEMF obtained an effect size of 0.48. Conclusion . Active T-PEMF was found superior to sham T-PEMF within the pharmacopsychometric triangle with a clinically significant effect size level above 0.40.